Holocene variability in the intensity of wind‐gap upwelling in the tropical eastern Pacific. (24th August 2015) - Toth, Lauren T.; Aronson, Richard B.; Cheng, Hai; Edwards, R. Lawrence
Abstract: Wind‐driven upwelling in Pacific Panamá is a significant source of oceanographic variability in the tropical eastern Pacific. This upwelling system provides a critical teleconnection between the Atlantic and tropical Pacific that may impact climate variability on a global scale. Despite its importance to oceanographic circulation, ecology, and climate, little is known about the long‐term stability of the Panamanian upwelling system or its interaction with climatic forcing on millennial time scales. Using a combination of radiocarbon and U‐series dating of fossil corals collected in cores from five sites across Pacific Panamá, we reconstructed the local radiocarbon reservoir correction, Δ R, from 6750 cal B.P. to present. Because the Δ R of shallow‐water environments is elevated by upwelling, our data set represents a millennial‐scale record of spatial and temporal variability of the Panamanian upwelling system. The general oceanographic gradient from relatively strong upwelling in the Gulf of Panamá to weak‐to‐absent upwelling in the Gulf of Chiriquí was present throughout our record; however, the intensity of upwelling in the Gulf of Panamá varied significantly through time. Our reconstructions suggest that upwelling in the Gulf of Panamá is weak at present; however, the middle Holocene was characterized by periods of enhanced upwelling, with the most intense upwelling occurring just after of a regional shutdown in the development of reefs at 4100 cal B.P. Comparisons with regional climate proxies suggest that, whereas the Intertropical Convergence Zone is the primary control on modern upwelling in Pacific Panamá, the El Niño–Southern Oscillation drove the millennial‐scale variability of upwelling during the Holocene. Key Points: The wind‐gap upwelling system in Pacific Panamá was present by 6750 cal B.P. Modern upwelling in the Gulf of Panamá was weak relative to the middle Holocene ENSO was the primary driver of upwelling in Pacific Panamá during the Holocene